Implication of Sexual Dimorphism and Reproductive Hormones in the Pathogenesis and Outcome of Postresuscitative Disease - A. V. Volkov; M. Sh. Avrushchenko; N. A. Gorenkova; Yu. V. Zarzhetsky (Общая реаниматология, 2006)
The paper summarizes the results of the authors’ own experimental studies and the data available in the literature on the implication of the neuroendocrine system, sexual dimorphism and reproductive hormones in the pathogenesis and outcome of postresuscitative disease. There is evidence for the important role of systemic hormonal balance and particularly endogenous and exogenous sex hormones in postresuscitative rehabilitative processes.